The Paradoxes of the Spiritual Self: Disidentification as a Marker of Identity. - Zaidman, Nurit; Pagis, Michal (Journal for the Scientific Study of Religion (John Wiley & Sons, Inc.), 2026)
This study examines how practitioners of self‐spirituality conceptualize their spiritual identity. On the basis of 62 in‐depth interviews with secular Jewish Israelis engaged in various spiritual practices, we find that spiritual identity is constructed through a distinctive cultural logic we term disidentification—a systematic resistance to conventional markers of identity. Although participants affirm spirituality as central to "who I am," they simultaneously reject understandings of identity as stable, coherent, socially anchored, constant, or distinctive. Each dimension involves a paradox: Practitioners find stability in commitment to remain unstable, achieve constancy through embracing intermittence, and construct coherent self‐narratives around the refusal of coherence. We show how disidentification intersects with other salient identities, and how its paradoxical structure provides practical resources for navigating between spiritual aspirations and social demands. Contributing to debates on spiritual fluidity versus coherence, we demonstrate that fluidity itself constitutes the shared cultural logic of spiritual identity.